Acute High-Intensity Interval Exercise Improves Inhibitory Control Among Young Adult Males With Obesity - Xie, Chun; Alderman, Brandon L.; Meng, Fanying; Ai, Jingyi; Chang, Yu-Kai; Li, Anmin (Frontiers in Psychology, 2020)
Objective: The purpose of the present study was to determine the influence of acute high-intensity interval exercise (HIIE) on neural and behavioral measures of inhibitory control in young male adults with obesity. Design: The present study employed a within-subjects design. Methods: Sixteen male adults with obesity (body mass index, BMI > 28 kg/m2) were recruited. Reaction time and response accuracy of the Flanker task as well as P3 and late positive potential (LPP) event-related potential (ERP) components, were measured following HIIE and a sedentary control in counterbalanced order. The HIIE session consisted of 30-minutes of stationary cycle exercise (5-min warm-up, 20-min HIIE, and a 5-min cool-down), whereas the control condition consisted of a time and attention-matched sedentary resting session. Results: Faster response times were observed following HIIE regardless of Flanker task condition. Faster and more accurate responses were also observed for congruent relative to incongruent conditions across both sessions. Relative to the neuroelectric data, acute HIIE resulted in increased LPP amplitude but did not affect P3 amplitude. Conclusion: These findings suggest that a single bout of HIIE results in a general beneficial effect on basic information processing and inhibitory control among obese male adults. While acute HIIE had limited effects on P3 component amplitude, this finding might reflect the influence of exercise (mode, duration) or subject (young obese males) level characteristics. The influence of acute HIIE on LPP amplitude suggests an exercise-induced enhancement in the ability to successfully maintain attention during the presentation of distracting irrelevant stimuli to achieve successful inhibition.